Pengembangan Media Sosial Instagram dan TikTok sebagai Sarana Branding dan Edukasi di BSI Kabupaten Tangerang - Arinata, Kadek Wika; Savera, Shan; Khasanah, Iftha Nikmatul; Prastowo, Marsya Aqila; Nuraprilia, Dyah; Beat, Sebastiana Laura; Hartono, Kennard Kurniadi; Purba, Delima Ester; Deliberto, Felicio; Nurhayati, Nurhayati (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The development of Instagram and TikTok as branding and educational tools for the Main Waste Bank of Tangerang Regency has shown significant results in increasing visibility and community participation in waste management. Through an integrated content marketing approach, the program successfully expanded the reach and engagement of BSI KabTang's social media accounts, with Instagram followers growing to 7136 and TikTok followers reaching 3935 within three months. Educational content presented in various formats, such as infographics, short videos, and interactive posts, effectively raised public awareness about the 3R principles (Reduce, Reuse, Recycle) and sustainable waste management practices. The main challenges included limited digital infrastructure and the digital literacy of the management team, which were addressed through intensive mentoring and sustainability strategies, including staff training, guidebook development, and building collaborative networks with environmental communities. This program demonstrated that social media can be an effective tool for environmental campaigns. Moving forward, the development of more interactive digital platforms and collaborations with various stakeholders is recommended to enhance the program's impact